2010
DOI: 10.1246/cl.2010.856
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Practical Method for the Preparation of a Branched Oligoglycerol with Acetonide Protection Groups

Abstract: A novel method for the preparation of 1,3-bis(2,2-dimethyl-1,3-dioxan-5-yloxy)propan-2-ol, a branched oligoglycerols (BGL), was developed from 1,3-diallylated glycerol in excellent yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…BGL003 (1,3-bis[(2,2-dimethyl-1,3-dioxan-5-yl)oxy]-2-propanol) and fenofibrate-BGL003 conjugate (FF-BGL) (Fig. 1C) were synthesized as described elsewhere Nemoto et al, 2007bNemoto et al, , 2010Nemoto et al, , 2012c.…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…BGL003 (1,3-bis[(2,2-dimethyl-1,3-dioxan-5-yl)oxy]-2-propanol) and fenofibrate-BGL003 conjugate (FF-BGL) (Fig. 1C) were synthesized as described elsewhere Nemoto et al, 2007bNemoto et al, , 2010Nemoto et al, , 2012c.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Therefore, we have designed symmetrically branched oligoglycerols (BGL) such as the trimer (BGL003) (Fig. 1A), of which molecular weight is as small as 240.25, as alternative highly hydrophilic modular molecules and have shown that stability in circulation and water-solubility of such molecules as proteins, liposomes and hydrophobic compounds were much improved by conjugation to BGL (BGLation) (Ishihara et al, 2010Nemoto et al, 1999Nemoto et al, , 2007aNemoto et al, , 2007bNemoto et al, , 2010Nemoto et al, , 2011Nemoto et al, , 2012aNemoto et al, and 2012bYamaguchi et al, 2008). Albeit these beneficial effects of BGLation, little was known whether BGL could be used in safety.…”
Section: Introductionmentioning
confidence: 99%
“…1B). We have successfully improved stability in circulation and water-solubility of such molecules as proteins, liposomes and hydrophobic compounds by conjugation to BGL to date (Ishihara et al, 2010(Ishihara et al, , 2012Nemoto et al, 1999Nemoto et al, , 2007aNemoto et al, , 2007bNemoto et al, , 2010Nemoto et al, , 2011Nemoto et al, , 2012aNemoto et al, and 2012bYamaguchi et al, 2008). In the accompanying paper, we demonstrated that hydrophilicity and water-solubility of fenofibrate, a quite hydrophobic anti-hyperlipidemic drug (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we have designed symmetrically branched oligoglycerols (BGL) such as the trimer (BGL003) (Figure A) as alternative small uniform highly hydrophilic modular molecules. We have successfully improved stability in circulation and water solubility of such molecules as proteins, liposomes, and hydrophobic compounds by conjugation to BGL to date. In addition, we have demonstrated biological safety of BGL003, the simplest BGL in cultured cells and rodents, suggesting BGL is innoxiously applicable to a prodrug. , However, it remained unclear whether the molecular modification by conjugation to BGL actually improves ADME properties of pharmaceuticals in terms of pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%